Probiotication of Bifidobacterium Spp. in dairy and non-dairy mango juice medium – A Green approach - Dorathy Pushparani, Dorathy Dorothy (Indian Journal of Dairy Science, 2021)
Mango (Mangifera indica L.) is a climacteric, tropical drupe of the Anacardiaceae family. This study aims at determining the ideal synbiotic combination using mango as a natural prebiotic source in two different mediums, dairy, and non-dairy, for two different probiotics Bifidobacterium infantis and Bifidobacterium lactis. Skimmed milk and sugarcane were observed on analysis to promote the growth of these probiotics and were the chosen dairy and non dairy substrates used in combination with mango. The ideal synbiotic combination of Mango with dairy /non dairy medium was optimized on the basis of sensory evaluation supported by total viable counts. Fermentation for 4 hours of the ideal synbiotic combinations with 0.1% innoculum of probiotic cultures was done. The 3:7 ratio of mango: skimmed milk and  mango : sugarcane with 4 hours of incubation gave desirable results with increasing microbial counts ,drop in  pH  and nominal increase  in acidity as fermentation time progressed. This ideal combination of probiotics with mango in both dairy and non dairy medium could be a promising blend in the food and beverage industry for formulating naturally functional products.